An analytic Volterra-series-based model for a MEMS variable capacitor. - Innocent, M.
Microelectromechanical systems (MEMS) components are gradually finding their way in communication applications. To fully understand their behavior in electrical circuits, an interpretable model is required that, in addition, can be simulated efficiently. This paper presents a model for a MEMS variable capacitor (varicap), that can be evaluated much more efficiently and equally accurate during circuit simulation than the differential equations that are normally used to describe this component. The model, based on Volterra series, describes the frequency dependence (e.g., the mechanical resonance) in combination with the nonlinear behavior of the MEMS varicap. The model is simple enough such that it can be interpreted by designers who want to use the MEMS varicap in RF communication circuits.
Keywords: MEMS variable capacitor; MEMS varicap; RF communication circuits; RFIC; Analytic Volterra-series-based model; Behavioral model; Circuit simulation; Frequency dependence; Mechanical resonance; Microelectromechanical systems; Nonlinear behavior